"Chrysalis Years:" Reading Christine Montalbetti During the Pandemic. Issue 3 (28th June 2022) - Brand, Philippe
Abstract: As the pandemic stretched on and on, the temptation to escape into the realm of fiction was very strong. This article focuses on Christine Montalbetti's novels Mon ancêtre Poisson (2019) and Journée américaine (2009), exploring the ways in which those novels thematize the time and the distance that can separate us from our loved ones, while the unique temporalities of her fiction illuminate in novel ways the lived experience of pandemic time. Montalbetti's writing opens up onto a theoretical space of virtual dialogue and communion with the reader, expanding the horizons of fiction and inviting readers inside.